2006
DOI: 10.1136/bjsm.2005.024513
|View full text |Cite
|
Sign up to set email alerts
|

Use of β2agonists in sport: are the present criteria right?

Abstract: Background: The regulations for doping control prohibit the use of b 2 agonist bronchodilators (salbutamol, salmeterol, formoterol, and terbutaline) unless the subject follows the procedure known as abbreviated therapeutic use exemption (ATUE). Objective: To highlight how the interest in discovering possible cheats may result in damage to athletes who really need bronchodilator treatment. Methods: Thirty one high level athletes (18 men and 13 women) with a previous diagnosis of asthma were examined in our labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Athletes can demonstrate EVH negative, but still experience EIB for a number of reasons, including being well-controlled with inhaled corticosteroids, being in a period of remission or the EIB being linked to specific allergens such as pollution or pollen. Furthermore, some studies have suggested that the cut-off criterion used to diagnose EIB following recognised bronchoprovocation is not suitable for elite athletes and may result in athletes with EIB being denied the most effective therapeutic treatment(s) 2224. Therefore, an athlete who is EVH negative, but has either symptoms and/or a previous diagnosis of EIB, should not immediately be deemed EIB negative.…”
Section: Discussionmentioning
confidence: 99%
“…Athletes can demonstrate EVH negative, but still experience EIB for a number of reasons, including being well-controlled with inhaled corticosteroids, being in a period of remission or the EIB being linked to specific allergens such as pollution or pollen. Furthermore, some studies have suggested that the cut-off criterion used to diagnose EIB following recognised bronchoprovocation is not suitable for elite athletes and may result in athletes with EIB being denied the most effective therapeutic treatment(s) 2224. Therefore, an athlete who is EVH negative, but has either symptoms and/or a previous diagnosis of EIB, should not immediately be deemed EIB negative.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the acute use of the current inhaled β 2 ‐AR agonist anti‐asthma medications by non‐asthmatic or asthmatic athletes seems unlikely to provide any improvement in performance in addition to that provided by the control of their condition. Of more concern is the adequacy of the tests required to obtain a therapeutic use exemption, as they may be inappropriate for diagnosing exercise‐induced asthma under the conditions experienced in competition ( Naranjo Orellana et al ., 2006 ).…”
Section: Drugs Used In Sport Acting Directly On β‐Arsmentioning
confidence: 99%
“…The test is considered positive if the decline in FEV 1 is greater than 20% from baseline value (FEV 1 measurements at rest). The fall in FEV 1 must be presented with a methacholine concentration of less than or equal to 8 mg/ml [ 6 , 7 ] . The test is useful in the clinic to diagnose chronic asthma, but has a low sensitivity for the screening of EIA.…”
Section: Resultsmentioning
confidence: 99%